ASPEK SOSIAL NOVEL DUA CINTA NEGERI SAKURA KARYA IRENE DYAH - Arbi Hildansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
AbstractNovel Dua Cinta Negeri Sakura is one of the novels by Irene Dyah. This novel by Irene Dyah does not only tell about romance but an interesting social point of view. What are the values of the social aspects contained in the novel Dua Cinta Negeri Sakura and how do the readers influence society from the social aspects in the novel Dua Cinta Negeri Sakura. The aim is to describe the influence of the social aspects of the novel on the reader. In this study, researchers used descriptive qualitative methods. Then, the technique used by the author is literature study technique. Any data that has been recorded in the form of a page number sentence and the paragraph number listed. The data resulting from this study are in the form of a big picture of several sentences that contain social aspects. Then, describe the influence of the social aspects of the sentence on the reader. The results of this study, the aspects contained in the novel Dua Cinta Negeri Sakura by Irene Dyah, namely the values of religion, culture, morals, education, economy, social environment. Then, the effect obtained on these values can influence it not only in theory, but the reader will apply it in real life or to the surrounding community.